Pengaruh Mendengarkan Instrumental Klenengan Gending Jawa Klasikterhadap Tekanan Darah Pasien Hipertensi - Didit Damayanti; Muhammad Taukhid; Yuli Anita Rahayu (STIKES Karya Husada Kediri, 2019)
Listening to instrumental with classical Javanese music is a type of complementary therapy that helps lower blood pressure. This study aims to determine the effect of listening to the instrumental with classical Javanese music toward blood pressure of hypertensive patients in Semen Village, District Pagu-Kediri. Design used pra eksperimental one group pre-post test design. Respondents given interventions 1 time a week for 8 minutes, and repeated 5 weeks with a sample of 40 respondents. Technique sampling with purposive sampling. Using statistical test Wilcoxon with α = 0,05. Statistical test results show Sig Pvalue = 0,000 < = 0,05. Then concluded that of listening to the instrumental with classical Javanese music toward blood pressure of hypertensive patients effective used lower blood pressure. Listening to the instrumental with classical Javanese music is fundamental as internal pusher in hypertensive patients in the process of healing stimulates alpha waves then increases hormone serotonin and hormone endorphins. It is recommended to hypertensive patients do therapy of listening instrumental with classical Javanese music routinely to accelerate the healing phase.